First molecular approach to diagnose paediatric pulmonary lophomoniasis: A case series. Issue 5 (31st March 2022) - Taheri, Amirmasoud; Fakhar, Mahdi; Nakhaei, Maryam; Banimostafavi, Elham Sadat; Masiha, Farzad; Ghaffari, Javad; Sheydai, Soroush; Rezaei, Mohammad Sadegh; Sharifpour, Ali
Abstract: A prospective study was conducted from 2017 to 2021 at Bouali Hospital in Mazandaran province, Sari, Iran. Out of 58 patients who were enrolled in our study, lophomoniasis was diagnosed in bronchoalveolar lavage fluid of nine patients, for the first time, using an in‐house polymerase chain reaction technique. All patients were treated with metronidazole at 7.5 mg/kg/day every 12 h for 14 days. After 6 months of follow‐up, symptoms were fully resolved. Abstract : Respiratory infections are one of the most common reasons for children being admitted to paediatric wards. Here, we present a case series in which all paediatric pulmonary lophomoniasis patients were diagnosed using the polymerase chain reaction approach, which was first described by Fakhar and colleagues